A new multilevel inverter with reduced switch count for renewable power applications - Seong-Cheol Kim; S. Narasimha; Surender Reddy Salkuti (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper proposes a new technique for a voltage source multilevel inverter (MLI) with reduced switch count, and it creates a smoother sinusoidal output waveform with reduced total harmonic distortion (THD). Therefore, the proposed technique identifies a better position in the list of multilevel converters used for power quality conditioners. Semiconducting devices are added to it if the number of levels increases. In this work, the topology of MLI with reduced number of switches is presented. A new MLI is proposed with lower number of switches and sources in order to achieve higher level. The proposed topology is framed out with the combination of three half bridge and a single H-bridge configuration. Detailed simulation results for 15-level inverter of single and three phase inverters are presented in this paper. Three phase 15-level inverter is developed by employing three isolated different renewable sources and 21 switches.